Baseflow measurement in mountain rivers using LSPIV: A case study of the Tarqui and Yanuncay rivers in the Ecuadorian Andes - Santiago A. Ochoa-García; Leandro Massó; Antoine Patalano; Carlos M. Matovelle-Bustos; Paola V. Delgado-Garzón (Revista de Teledetección)
This study is motivated by the difficulty of applying experimental techniques to characterize base flows in mountain rivers. Intrusive instruments are not optimal for measuring low flow rates, as they require a minimum depth to be submerged and to measure flow velocity. The LSPIV methodology was applied using an Autel Evo II RTK Series 3 UAV. The results were validated through measurements taken with a Redback current meter, showing that the flow rates and velocity fields obtained with the presented techniques are of the same order of approximation. The flow velocity fields resulting from the application of LSPIV enabled the identification of typical flow characteristics in mountain rivers with gravel and boulder beds: zones of acceleration and turbulent mixing, stagnation areas due to obstacles within the flow, flow recirculation, and shear regions caused by interaction with existing morphological structures. Thus, the LSPIV technique is presented as a valuable tool for characterizing extreme flows in mountain rivers using non-intrusive methods.